2014
DOI: 10.1111/jmwh.12173
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Personal Knowledge and Decision Self‐Efficacy in Choosing Trial of Labor After Cesarean

Abstract: In this study, more knowledge about the risks and benefits of TOLAC and ERCD was found to be positively associated with the decision for TOLAC. This finding is important for health care providers when counseling women who have had a prior cesarean about their choices regarding mode of birth during a subsequent pregnancy. Supplying women with complete and accurate information about the risks and benefits of both choices may help increase the number of women who opt for TOLAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…[44][45][46][47] Increased knowledge about the risks and benefits associated with VBAC versus repeat cesarean was found to be positively associated with the decision to labor after cesarean. 53 However, Bernstein et al reported that at the time of admission for birth, many women continued to demonstrate a lack of knowledge about risks and benefits of repeat cesarean versus VBAC. 54 These knowledge deficits about birth options after previous cesarean may constrain women's choices to seek access to VBAC.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] Increased knowledge about the risks and benefits associated with VBAC versus repeat cesarean was found to be positively associated with the decision to labor after cesarean. 53 However, Bernstein et al reported that at the time of admission for birth, many women continued to demonstrate a lack of knowledge about risks and benefits of repeat cesarean versus VBAC. 54 These knowledge deficits about birth options after previous cesarean may constrain women's choices to seek access to VBAC.…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings are reassuring about risks and benefits of VBAC driving women's plans, there are indications that some women who may be appropriate candidates for VBAC do not have an opportunity to make this choice. For example, other studies have found that women with a prior cesarean had overall low knowledge about risks and benefits of both options . One study found that women choosing a trial of labor after cesarean had higher levels of knowledge than women choosing repeat cesarean, but 45% of women choosing trial of labor were still classified as having low knowledge .…”
Section: Discussionmentioning
confidence: 99%
“…31,33 One study found that women choosing a trial of labor after cesarean had higher levels of knowledge than women choosing repeat cesarean, but 45% of women choosing trial of labor were still classified as having low knowledge. 31 This underscores the need for patient education in addition to clinical recommendations when assisting women in making a decision about VBAC. Notably, however, when describing reasons for future delivery mode preferences, not a single person mentioned a provider being encouraging of VBAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those women in this study had a higher perceived knowledge about normal birth and cesarean before the intervention than their counterparts did. However, this knowledge does not seem sufficient to impact the type of birth outcome, even though higher knowledge about the risks of Csection increases the chance of women waiting for labor onset and avoiding scheduling an elective surgery (75).…”
Section: Creating Tailored Health Education Interventionsmentioning
confidence: 99%